Mothering as a Psychlogical Process: A Grounded Theory Exploration - Barlow, Constance A.; Cairns, Kathleen V. (Canadian Journal of Counselling and Psychotherapy, 2007)
The purpose of this study was to characterize the psychological experience of mothering. By asking the broad research question, "What are the psychological processes women experience as they move from childlessness through the first twelve years of mothering?," a grounded theory was developed representing the processes of mothering. Unstructured interviews were conducted with 11 mothers who had one or more children under 12 years of age. The grounded theory is comprised of two linear time dimensions, Engagement and Immersion. Predominant psychological processes associated with each dimension were identified and counselling implications are discussed.